Obowiązek władz publicznych do prowadzenia polityki sprzyjającej zaspokojeniu potrzeb mieszkaniowych a proces starzenia się społeczeństwa - Kuchciak, Anna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
Article 75 (1) of The Constitution of the Republic of Poland obliges public authorities to pursuepolicies conducive to satisfying the housing needs of citizens. Ongoing demographic change – theageing of society – requires consideration of the issue of seniors also in the sphere of housing. Thisarticle takes up this subject and concisely presents the constitutional regulations, as well as brieflyhighlights other legal solutions that could affect satisfying the housing needs of elderly people
Keywords: zaspokajanie potrzeb mieszkaniowych; starzenie się społeczeństwa; osoby starsze